Efficaccy of probiotic in the treatment of small intestinal bacterial overgrowth. Systematic review and meta-analysis - Niño, Sebastian Fernando (2024)
Introduction: Conventional management of small intestinal bacterial overgrowth (SIBO) involves intraluminal-action antibiotics. Controversially, probiotics are used to optimize outcomes, but this therapeutic intervention is understudied. Objective: To evaluate the efficacy of probiotics in the treatment of small intestinal bacterial overgrowth. Materials and methos: A search was conducted using relevant terms guided by a documentalist in CENTRAL, MEDLINE, and EMBASE, LILACS, conference proceedings, the International Clinical Trials Registry Platform (ICTRP), and ClinicalTrials.gov, in English or Spanish, up to January 2023. The search aimed to identify studies evaluating the effectiveness of probiotics in small intestinal bacterial overgrowth. Controlled trials of probiotics compared to placebo or other interventions (antibiotics) for symptom control and normalization of hydrogen breath test in adult patients with small intestinal bacterial overgrowth were included. Two authors independently assessed and extracted data. Information on methods, participants, interventions, and outcomes (resolution of SIBO by hydrogen breath test, symptom control) was collected. When appropriate, risk ratios (OR) with 95% confidence intervals (CI) were calculated. Study quality was evaluated using the Cochrane Risk of Bias Assessment Tool. Results: A total of 18 clinical trials were found, including one case-control study, two crossover trials, and one single-arm clinical trial. Out of these, 14 clinical trials had a control group, of which 9 were randomized, collecting information from 496 patients treated with probiotics and 480 controls. Among them, 6 clinical trials compared probiotics (n=122) against placebo (n=104). Due to lack of uniformity in outcome reporting, only 3 of these studies were included in the meta-analysis, revealing a favorable effect of probiotics in resolving SIBO by hydrogen breath test (OR=0.3, 95% CI, 0.3-1.0). The studies showed high heterogeneity and a high risk of bias. Conclusions: Using the GRADE methodology, we found low-quality clinical evidence in favor of using probiotics compared to placebo for the resolution of SIBO.